2009
DOI: 10.1016/j.resp.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Medullary serotonin neurons and central CO2 chemoreception

Abstract: Serotonergic (5-HT) neurons are putative central respiratory chemoreceptors, aiding in the brain's ability to detect arterial changes in P CO 2 and implement appropriate ventilatory responses to maintain blood homeostasis. These neurons are in close proximity to large medullary arteries and are intrinsically chemosensitive in vitro, characteristics expected for chemoreceptors. 5-HT neurons of the medullary raphé are stimulated by hypercapnia in vivo, and their disruption results in a blunted hypercapnic ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
131
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 119 publications
(180 reference statements)
11
131
1
Order By: Relevance
“…It has previously been shown that 5-HT neurons are required for a normal ventilatory response to hypercapnia (9,13,29,30). The results presented here indicate that 5-HT neurons are also required for a normal arousal response to hypercapnia.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It has previously been shown that 5-HT neurons are required for a normal ventilatory response to hypercapnia (9,13,29,30). The results presented here indicate that 5-HT neurons are also required for a normal arousal response to hypercapnia.…”
Section: Discussionsupporting
confidence: 64%
“…In vitro studies have shown that a subset of 5-HT neurons in both the medullary and midbrain raphé increases firing rate in response to a rise in CO 2 or decrease in pH (9). When studied in unanesthetized behaving mammals, similar results have been obtained in vivo by multiple groups (9).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Another possibility is that the RTN is an obligatory intermediate for funneling input from other central chemoreceptors to the RRG early but not later in life, although experimental evidence for this is still lacking. Candidate chemoreceptor sites are serotonergic neurons that have been reported to be virtually pH-insensitive at birth and to become fully operational only beyond the newborn period (Wang and Richerson, 1999;Corcoran et al, 2009) but also glial cells (Gourine et al, 2010;Wenker et al, 2010). The latter respond to low pH already in young postnatal rats and may act mainly via RTN neurons, but additional pathways may come into play in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonergic (5-HT) neurons, located in the rostral ventrolateral medulla, are putative central chemoreceptors. There is compelling evidence now that there are multiple additional sites of central chemoreception 5 (see for a review). Ventilatory response to CO 2 is significantly reduced in preterm infants but increases with advancing postnatal age.…”
Section: Central Chemoreceptors and Impaired Hypercapnic Ventilatory mentioning
confidence: 99%